Evaluasi Atas Metode Alokasi Overhead Menurut Departemen terhadap Penetapan Harga Pokok Produksi : Studi Kasus Pada PT. Sonoco Indonesia - Setiawan, H. Hendra (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2005)
Deciding on the tariff of overhead of a factory per department of production uses direct working hours for all the departments of production. This is determined in order to make it easier for management to determine the kilogram per direct worker. Determining the basic price of POY production at PT Sonoco in 2003 reached Rp. 13,409,257.67 where the biggest cost goes to the direct material. This is due to the increase price of pulp in every quarter in 2003. In determining production basic price, economizing direct material is implemented by using raw material stock which is slow moving. The rate is maximum in line with the implementation of quality control of production, in order to increase the production efficiency. Key words: Overhead Cost; Production Cost.